Peran Aktif Orang Tua dalam Mempersiapkan Kematangan Anak Sebelum Memasuki Sekolah Dasar - Fina Khoerunisa; Umi Hasanah; Nia Novita; Natasha; Sugiana; Naili Rohmah (PT Pustaka Cendekia Publisher, 2025)
The transition period from kindergarten to elementary school is a crucial stage that requires comprehensive readiness from children, both cognitively, emotionally, socially, and physically. This readiness does not emerge suddenly but is shaped through a continuous nurturing process and support from the immediate environment, particularly from parents. The parenting activities conducted at Aisyiyah Bustanul Athfal 49 Kindergarten in Semarang on Saturday, May 31, 2025, aim to enhance parents' understanding of the importance of their role in preparing children for the elementary education phase. Through an educational and dialogic approach, the activity encouraged parents to be more aware of their parenting responsibilities, which are not only focused on academic aspects but also on character development and children's independence. Evaluation of the activity showed an increase in participants' knowledge of effective support strategies, such as establishing daily routines, assigning small responsibilities, and supporting children in social interactions. This activity emphasizes that consistent and role-aware parental involvement is key to helping children achieve the maturity needed before entering elementary school.